2016
DOI: 10.1002/jcph.779
|View full text |Cite
|
Sign up to set email alerts
|

Can Bias Evaluation Provide Protection Against False‐Negative Results in QT Studies Without a Positive Control Using Exposure‐Response Analysis?

Abstract: The revised ICH E14 document allows the use of exposure-response analysis to exclude a small QT effect of a drug. If plasma concentrations exceeding clinically relevant levels is achieved, a positive control is not required. In cases when this cannot be achieved, there may be a need for metrics to protect against false-negative results. The objectives of this study were to create bias in electrocardiogram laboratory QT-interval measurements and define a metric that can be used to detect bias severe enough to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 24 publications
0
42
0
Order By: Relevance
“…Analysis of drug‐related QT/QTc‐interval changes relative to plasma PK concentrations were conducted on all dose regimens in this part of the study. The ECGs used for this analysis required adjudication by qualified cardiologists in accordance with principles set out in the International Conference on Harmonisation (ICH) E14 guideline and subsequent question‐and‐answer documents . The principles of this analysis follow the statistical methods described by Garnett et al .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of drug‐related QT/QTc‐interval changes relative to plasma PK concentrations were conducted on all dose regimens in this part of the study. The ECGs used for this analysis required adjudication by qualified cardiologists in accordance with principles set out in the International Conference on Harmonisation (ICH) E14 guideline and subsequent question‐and‐answer documents . The principles of this analysis follow the statistical methods described by Garnett et al .…”
Section: Methodsmentioning
confidence: 99%
“…The ECGs used for this analysis required adjudication by qualified cardiologists in accordance with principles set out in the International Conference on Harmonisation (ICH) E14 guideline and subsequent question-and-answer documents. [16][17][18][19][20][21][22][23] The principles of this analysis follow the statistical methods described by Garnett et al 24 The effects of a meal on the ECG were used to establish assay sensitivity, that is, the ability of the study to detect small changes in the QTc. 22,25…”
Section: Cardiac Assessmentsmentioning
confidence: 99%
“…Moreover, the proposed quality metric does not specifically address those types of error that could cause false‐negative results, that is, a negative bias for long QT intervals and a positive one for short QT intervals. More recently, Ferber et al (2017) investigated a measure constructed to specifically identify bias that could lead to false‐negative results by comparing the reported QTc values with those obtained by standard algorithms on continuous Holter recordings without any human intervention . This method, although promising, needs further validation before it can be applied widely.…”
Section: Discussionmentioning
confidence: 99%
“…Other methods of ensuring assay sensitivity as recommended by ICH E14 are therefore needed. Methods for bias evaluation were also considered to increase the confidence in the data collected from the IQ‐CSRC study . This published study demonstrated that significant bias has to be introduced to cause false‐negative results.…”
mentioning
confidence: 99%
“…In addition, the use of a positive control is not recommended as long as there is a placebo group and drug concentrations achieved are a multiple of the clinically relevant exposure. In addition, to mitigate against a false-negative study in cases where insufficient drug exposure occurs, method bias sensitivity (MBS) analysis [45] has been proposed by several stakeholders using the slope estimate of Bland-Altman plots as an indicator of potential bias. A bias severity <−10 msec over a range of QTcF values was proposed as the threshold measure that would confer a <5% false-negative rate of drug-mediated QT prolongation.…”
Section: Dawn Of a New Paradigm For Drug Cardiovascular Liabilitymentioning
confidence: 99%